Role of EMT in Metastasis and Therapy Resistance - Smith, Bethany N. (J Clin Med, 2016)
Epithelial–mesenchymal transition (EMT) is a complex molecular program that regulates changes in cell morphology and function during embryogenesis and tissue development. EMT also contributes to tumor progression and metastasis. Cells undergoing EMT expand out of and degrade the surrounding microenvironment to subsequently migrate from the primary site. The mesenchymal phenotype observed in fibroblasts is specifically important based on the expression of smooth muscle actin (α-SMA), fibroblast growth factor (FGF), fibroblast-specific protein-1 (FSP1), and collagen to enhance EMT. Although EMT is not completely dependent on EMT regulators such as Snail, Twist, and Zeb-1/-2, analysis of upstream signaling (i.e., TGF-β, EGF, Wnt) is necessary to understand tumor EMT more comprehensively. Tumor epithelial–fibroblast interactions that regulate tumor progression have been identified during prostate cancer. The cellular crosstalk is significant because these events influence therapy response and patient outcome. This review addresses how canonical EMT signals originating from prostate cancer fibroblasts contribute to tumor metastasis and recurrence after therapy.